Punjab in prosperity and violence : administration, politics, and social change, 1947-1997 - Grewal, J. S.; Banga, Indu. (New Delhi : Published for K.K. Publishers for Institute of Punjab Studies, Chandigarh, 1998)
Chiefly on the political scene; papers presented at various seminars held during 1995-1997.
Includes bibliographical references.
Keywords: Punjab (India) -- Politics and government